Nanocomposites with size-controlled nickel nanoparticles supported on multi-walled carbon nanotubes for efficient frequency-selective microwave absorption. (8th February 2020) - Mederos-Henry, Francisco; Depaifve, Sébastien; Wolf, Arnaud; Danlée, Yann; Delcorte, Arnaud; Bailly, Christian; Huynen, Isabelle; Hermans, Sophie
Abstract: Two types of nanocomposites based on multiwalled carbon nanotubes (MWCNTs) decorated with metallic nickel nanoparticles (NiNPs) possessing very different size distributions (13 vs. 130 nm) were produced using novel synthetic techniques. The obtained nanocomposites were dispersed in a polycarbonate (PC) matrix to produce thin ( 500 μm) composite films. For the first time, we show that such films possess clear ferromagnetic resonances in the ultra-high frequency (UHF) and L microwave regions. Furthermore, we prove that their natural ferromagnetic (FMR) frequency is lowered when using nanocomposites with smaller NiNPs. These results could be exploited to design selective dual-band filters for telecommunications applications.